2022
DOI: 10.1007/s13201-021-01547-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding land use/land cover and climate change impacts on hydrological components of Usri watershed, India

Abstract: Land use/cover (LULC) and climate are significant environmental factors that influence watershed hydrology across the globe. The present study attempts to understand the consequences of existing changing patterns of climate and LULC on the hydrology of the Usri watershed. Different water balance components were simulated using a semi-distributed Soil and Water Assessment Tool (SWAT) model. Sixteen scenarios were generated using combinations of four periods of climatic data (1974–84; 1985–1995; 1996–2006 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 67 publications
1
15
0
1
Order By: Relevance
“…The Semampa River Basin, which was once covered in forests, today experiences climate conditions that are in between those of a forest and a savannah, making it more and more susceptible to water scarcity (Elizabeth, 2008). As more and more money is invested in water resource development to meet the growing demand for groundwater resources knowledge, groundwater resource trends, scope changes become important (Mukesh, et al, 2022) ; (Naeem, et al, 2020) and (Elizabeth, 2008). The expansion of agricultural land and urban areas into the forest has led to an increase in surface runoff due to precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The Semampa River Basin, which was once covered in forests, today experiences climate conditions that are in between those of a forest and a savannah, making it more and more susceptible to water scarcity (Elizabeth, 2008). As more and more money is invested in water resource development to meet the growing demand for groundwater resources knowledge, groundwater resource trends, scope changes become important (Mukesh, et al, 2022) ; (Naeem, et al, 2020) and (Elizabeth, 2008). The expansion of agricultural land and urban areas into the forest has led to an increase in surface runoff due to precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the future impact of the climate and land use change on hydrologic variables of the watershed is a thrust area of research in the eld of hydrology to understand the availability and distribution of water for different uses in near future (Kumar et al, 2022). Further, to study the sustainability of existing structures and for the development of innovative water resource management plans for a speci c basin or watershed can also achieved through such modelling studies.…”
Section: Introductionmentioning
confidence: 99%
“…Few scholars have investigated the isolated impact of future LULC on water balance component and suggested that catchment scale modi cations in LULC affects different water balance components of a basin (Kumar et al, 2018;Sertel et al, 2019;Kumar et al, 2022). Others have explored the isolated impact of climate on hydrologic components (Gashaw et al, 2018;Gong et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alih fungsi lahan yang tidak terkendali tentunya akan berdampak pada pendangkalan sungai, penurunan keanekaragaman hayati, dan penurunan kualitas lingkungan serta bencana alam yang sewaktu-waktu akan terjadi (Rakuasa et al, 2022c). Perubahan tutupan lahan perlu dikendalikan dan dipantau untuk menjamin fungsi ekosistem DAS (Kumar et al, 2022). Deteksi perubahan tutupan lahan sangat penting untuk pemahaman yang lebih baik tentang dinamika lanskap selama periode yang diketahui memiliki pengelolaan berkelanjutan (Salakory dan Rakuasa, 2022).…”
unclassified